2009
DOI: 10.1021/jp900813n
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonded Complexes of Phenylacetylene with Water, Methanol, Ammonia, and Methylamine. The Origin of Methyl Group-Induced Hydrogen Bond Switching

Abstract: The infrared spectra in the acetylenic C-H stretching region for the complexes of phenylacetylene with water, methanol, ammonia, and methylamine are indicative of change in the intermolecular structure upon substitution with a methyl group. High-level ab initio calculations at CCSD(T)/aug-cc-pVDZ level indicate that the observed complexes of water and ammonia are energetically the most favored structures, and electrostatics play a dominant role in stabilizing these structures. The ability of the pi electron de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
54
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 26 publications
(51 reference statements)
1
54
2
Order By: Relevance
“…, respectively, over the formation of PW1 and PW2 at 10 K. [33] The vibrational spectra and the energetics support the assignment of PW3 as the structure observed in the gas phase. It is interesting to note that the structure of the phenylacetylene-water complex is different from both benzene-water and acetylene-water complexes, [57][58][59][60][61] even though the phenylacetylene incorporates both the features of benzene and acetylene.…”
supporting
confidence: 59%
See 4 more Smart Citations
“…, respectively, over the formation of PW1 and PW2 at 10 K. [33] The vibrational spectra and the energetics support the assignment of PW3 as the structure observed in the gas phase. It is interesting to note that the structure of the phenylacetylene-water complex is different from both benzene-water and acetylene-water complexes, [57][58][59][60][61] even though the phenylacetylene incorporates both the features of benzene and acetylene.…”
supporting
confidence: 59%
“…Based on the FDIR spectrum (Figure 17 A) the formation of a CÀH···N hydrogen-bonded complex can be ruled out completely, as this complex would have a much lower acetylenic CÀH stretching frequency than complexes with ammonia and methylamine. [32,33,37] Further, the appearance of the Fermi resonance bands is also an indication that the acetylenic group of phenylacetylene is relatively unperturbed upon interaction with 1,3,5-triazine. In the case of phenylacetylene complexes with water, methylamine, and trifluoroethanol, we showed that the interaction of the solvent molecule with the p-electron density of the acetylenic CC bond leads to loss of Fermi mixing.…”
Section: The 135-triazine Complexmentioning
confidence: 99%
See 3 more Smart Citations